A Study on Consumer Buying Behaviour of Home Appliances with Reference to LG Products - Nasrin Sulthana, M.; Sakthivel Murugan, M. (Indian Journal of Marketing, 2011)
The research was conducted in Madurai city during the year 2006-07. Advanced research has been done in the year 2009. This is a study based on empirical research. The data were collected from both primary and secondary sources. Importance is given only to primary data. Though various statistical tools that are available for effective analysis, the researcher selected factor analysis, chi square test and weighted arithmetic mean to analyze various aspects with high standard and accuracy. Factor analysis was used to find factors determining the customers' preference for LG products using SPSS Package. Chi square test was used to find whether income level of customers will affect the mode of payment, and whether income level of customers will affect the satisfactory level of price of LG. One sample "t" test was done to analyze the factors influencing the purchase behavior of the home appliances.